"In my village, everyone uses the tractor": Gold mining, agriculture and social transformation in rural Burkina Faso. Issue 3 (July 2020) - Brugger, Fritz; Zanetti, Jessica
Highlights: Three out of four ASGM workers in Burkina Faso remit revenues to their families. Wie find four distinct patterns how informal gold miners combine agriculture and mining. Successful livelihood strategies try to increase agricultural productivity or to diversify. ASGM fosters a socio-economic differentiation and the formation of an ASGM based upper class in rural areas. Abstract: Artisanal and small-scale gold mining (ASGM) has become part of the livelihood strategy for a large section of the rural population in Burkina Faso. In some areas of the country, two out of three households have at least one family member working at an artisanal or small-scale mine. Whether this leads to a de-agrarianization of the rural area or rather to a diversification of livelihood strategies is debated. Using a mixed research methods approach, we analyze the interaction between agriculture and ASGM at the household level at four mining sites in the Center-North and North Regions of Burkina Faso. We focus, in particular, on how labor and capital are allocated, and how mine workers reinvest their eventual revenues. We find that both mine characteristics and time devoted to mining influence the extent to which livelihood strategies change over time. Mineworkers who fully engage with mining and choose to pursue work at productive mines are the most likely to step up their livelihoods or discontinue agricultural activities. Others who work on less productive mines to complement their income during the dry season are more likely to stagnate or even see their situation worsen. Our findings suggest that ASGM fosters a socio-economic differentiation and the formation of an ASGM-based upper class in rural areas. Graphical abstract: Image, graphical abstract